Phosphorylation of a novel SOCS-box regulates assembly of the HIV-1 Vif-Cul5 complex that promotes APOBEC3G degradation - Mehle, A (2015)
HIV-1 Vif (viral infectivity factor) protein overcomes the antiviral activity of the DNA deaminase APOBEC3G by targeting it for proteasomal degradation. We report here that Vif targets APOBEC3G for degradation by forming an SCF-like E3 ubiquitin ligase co